The Vietnamese Pig as a Translational Animal Model to Evaluate Tissue Engineered Heart Valves: Promising Early Experience. Issue 4 (April 2017) - Gallo, Michele; Poser, Helen; Bottio, Tommaso; Bonetti, Antonella; Franci, Paolo; Naso, Filippo; Buratto, Edward; Zanella, Fabio; Perona, Giovanni; Dal Lin, Carlo; Bianco, Roberto; Spina, Michele; et al.
Several animal models are currently used for the surgical implantation of either biologic or biopolymeric scaffolds in order to provide in vivo assessment of tissue-engineered heart valves. The Vietnamese pig (VP) is herein proposed as a suitable recipient to test the function of novel bioengineered valve substitutes, in the reconstruction of the right ventricular outflow tract (RVOT). This review aims to provide a complete and exhaustive panel of physiological parameters and methodological information for preclinical studies of tissue-engineered heart valves in the VP animal model.